ANALISIS PENERAPAN TOTAL PRODUCTIVE MAINTENANCE DAN KAIZEN UNTUK MENINGKATKAN OVERALL EQUIPMENT EFFECTIVENESS PADA LINE LIQUID DI PT.PTI - Zulheri Zulheri; Karel L Mandagie; Basuki Arianto (JURNAL TEKNOLOGI INDUSTRI, 2019)
Development and improvement efforts made by the pharmaceutical industry in the production sector, namely efforts to reduce down time and reduce defects and a machine is always high with down time and always produces product defects, of course, has decreased productivity, which ultimately disadvantages the company because of the ineffectiveness of the machine.To calculate and increase the level of effectiveness of a machine, an approach is needed, one approach that can be used is the method of calculating Overall Equipment Effectiveness (OEE) as a product of Total Productive Maintenance (TPM).The implementation of TPM and the formation of the Kaizen Team to increase the value of OEE has been very successful. Avaibility rate which previously averaged from January to April was 72.5% in May to 76.4%, and also the increase in the OEE value which was previously 69.9% in May increased to 73.0%. Previously, in January to April, an average of 6823 pcs in May decreased to 2722 pcs so that the rate quality increased, previously in January to April 2018 it was 99.4% in May 2018, it increased to 99.7%. Keyword : TPM, OEE, Kaizen